The adaptation of folk songs in the choral works of Kosovar composers (Música Hodie, 2026)
This study examines the structural, tempo rhythmic and textural models of folk song adaptation in choral music and traces the transformation of folk melody within professional choral writing. The research was conducted in three stages: a comparative analysis of choral arrangements of folk songs from Central, Western and Southern Europe; a reconstruction of the historical conditions that shaped the formation of choral culture in Kosovo; and a structural and analytical examination of four choral works by Kosovo composers, namely “Posht’ mizorët”, “Ani Çilma Derën”, “Gush Sharavelli” and “N’mjedis t’ballit”, based on folk melodies. The study identifies several stable European models of choral folklore adaptation, including the Hungarian model, characterised by the accurate transfer of field recordings into choral texture with varying harmonic complexity, the Moravian model, which emphasises irregular phrase structures and the preservation of linguistic and intonational formulas, and the English approach, oriented toward four part harmonisation and the dual national and universal function of the repertoire. It is shown that choral singing in Kosovo developed at the intersection of ancient polyphonic practices, Byzantine and Catholic liturgical traditions and the post war Yugoslav educational system, resulting in the close integration of folk song material into professional choral language. Analysis of Kosovo works reveals a typology of local adaptation approaches ranging from simple homophonic harmonisations for educational choirs to polyphonic strophic forms with asymmetrical metres, while also demonstrating a consistent dependence of compositional decisions on the modal, rhythmic and textual characteristics of the folklore source.